Design of a Vivaldi antenna with Electromagnetic Band Gap (EBG) structure: article / Ariff Ridzuan Mohammad - Mohammad, Ariff Ridzuan (2013)
This paper summames a detailed design of a Vivaldi Antenna with Electromagnetic Gap (EBG) structure. The Antenna is proposed at a height of 0.51 mm from the substrate Rogers RT/Duroid®5870 with nine squares of EBG structure. The EBG structure is placed at ground plane with copper cladding of 0.0175 mm The patch antenna structure was designed to resonate at frequency of 5.6 GHz This work is focused on designing the best Vivaldi antenna by collecting the best simulation result in terms of return loss (S 11 ), bandwidth (BW), radiation pattern of gain and directivity and voltage standing wave ratio (VSWR). The work is proceeded by combining Vivaldi antenna with EBG structure. This combination is to investigate the EBG structure characteristic in antenna design in order to increase the performance of antenna in term of return loss and bandwidth. Simulations and measurements have been carried out to verify the performance of Vivaldi antenna with and without EBG structure. All the simulation and measurement work is done by Computer Simulation Technology (CST) Studio Suite software and Vector Network Analyzer (VNA) respectively. The simulated and measured results are presented.